Dynamic measurement of moisture content using microwaves for moisture evaluation of agricultural products. Issue 2 (3rd January 2020) - Kon, Seitaro; Kato, Yuto; Horibe, Masahiro
Abstract: This paper describes a dynamic measurement method using correlations between phase and amplitude changes of microwaves for the moisture content of agricultural products such as rice and wheat. The proposed method does not require the value of the bulk density and/or the mass of the target. Static and dynamic measurements of rice with different moisture contents were performed. The results of the dynamic measurements were in close agreement with those of the static measurements. The ratio of the amplitude change and phase shift is linearly dependent on the moisture content of rice for both the static and dynamic measurements. Furthermore, it is possible to measure wrapped silage samples with a high moisture content directly. To optimize the measurement frequency, the relationships between the moisture content and phase–amplitude correlation was evaluated. As a result, an optimized frequency was obtained. The proposed method is available under conditions such as the range of moisture content from 10 to 80% with one optimized frequency. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.